Consoantes palatais como geminadas fonológicas no Português Brasileiro (Revista de Estudos da Linguagem, 2000)
ln this paper we observe that 1ft! behaves in many respectsdifferently from Im,nI. Whereas Im,nl can be preceded by abranching rhyme, /fi/ cannot. When /fi/ occurs between the lasttwo vowels of a word that is at least trisyllabic, stress can never'skip' the prefinal syllable. On the other hand, when Im,nI occupythe onset of a word-final syllable, proparoxitonic stress does occur(ébano, ágamo). Also, lfi/ does not occur word-initially, in whichposition Im,nI are frequendy found. Furthermore, syllable structuretypically splits a Nli,ul/ sequence into two syllables before [,(] and[fi], but not before Im,nI. Finally, before the palatal nasal, allophonicnasalisation of a preceding unstressed vowel is obligatory, whereasallophonic nasal spreading does not affect unstressed vowels beforeIm,nI. We will show that all these facts are readily explained bythe hypothesis that the palatal sonorants of BP are gerninateconsonants at the lexical leveI.